Presentation of the Modal Verbs in the German Textbook “Netzwerk neu A1”: Recommendations for Teaching Modal Verbs to Thai Learners - Charoengongit , Worapong; Unyamanee Chumpong, Unyamanee; Rerg-a-nun, Apinphorn (Manutsat Paritat: Journal of Humanities, 2022)
The aims of this article were to analyze how modal verbs are presented in the German textbook "Netzwerk neu" for Thai learners of A1 level and to suggest some teaching methods for such modal verbs to Thai learners of A1 level. Six modal verbs are presented in the textbook by their frequency of occurrence in everyday situations. The six modal verbs include können, müssen, wollen, mögen, sollen, and dürfen. The meanings and uses of each modal verb are conveyed through the presentation of different contexts of communication in daily life, in the forms of reading texts and dialogues. The learners notice the meaning and use of each modal verb themselves without explicit grammatical explanation through different exercises in the textbook. In order to use the textbook successfully, instructors should recognize such an approach on which this textbook is designed together with the specific characteristics of Thai learners with English as their first foreign language. The two important points could be a great supplement toward an effective approach for teaching German modal verbs to the Thai Learners of A1 level.